PREVALENCE OF DENTAL CARIES AND CHRONIC CATARRHAL GINGIVITIS IN SCHOOL-AGE CHILDREN IN DIFFERENT REGIONS OF UKRAINE - I.O. Trubka; O.A. Udod; N.O. Savychuk; L.V. Korniienko; S.I. Dramaretska; A.О. Savychuk (Український стоматологічний альманах)
Actuality. The study of the prevalence of dental caries and chronic catarrhal gingivitis (CCG) in schoolage children living in different regions of Ukraine is necessary to identify risk factors for their simultaneous development and to develop regionally targeted sets of preventive measures.